2019
DOI: 10.1063/1.5096579
|View full text |Cite
|
Sign up to set email alerts
|

Chemical mist deposition of organic for efficient front- and back-PEDOT:PSS/crystalline Si heterojunction solar cells

Abstract: We have investigated an n-type crystalline Si (n-Si) heterojunction solar cell with organic conductive polymer poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) on a plane and isotropically textured n-Si substrate by using chemical mist deposition (CMD). The PEDOT:PSS layer was deposited uniformly on isotropically textured n-Si with the increased passivation of surface defects of n-Si and stronger adhesion rather than the spin-coated film by adjusting deposition parameters. The power convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…S4, further confirming that the improved J sc for the SnCl 2 solution-treated devices is from the enhanced light absorption and further from the reduced light reflection because of the wrinkled surface of the MXene layers (see Fig. 2b) [56].…”
Section: Resultsmentioning
confidence: 56%
“…S4, further confirming that the improved J sc for the SnCl 2 solution-treated devices is from the enhanced light absorption and further from the reduced light reflection because of the wrinkled surface of the MXene layers (see Fig. 2b) [56].…”
Section: Resultsmentioning
confidence: 56%
“…On the other side, for the case of the absorber layer, the thickness of 1000 nm, doping concentration of 10 19 cm −3 , and defect density of 10 15 cm −3 are chosen as optimized conditions for further use. ( ) [36][37][38] .…”
Section: Resultsmentioning
confidence: 99%
“…Li et al reported a PCE of 5.68% for an 18 μm planar THSCs by introducing a 2 nm amorphous Si layer to passivate the interface, which enhances the lifetime and thus improves the device performance. 59 The efficiency of the SiNW-THSCs can be improved further by providing better PEDOT:PSS coating and Si contact using different coating methods such as mist deposition, 60 varying the viscosity or modifying polymer solution, 61 and by passivating the surface of Si. 62 Furthermore, the performance stability of flexible THSCs after bending was also investigated for a fresh set of samples.…”
Section: Resultsmentioning
confidence: 99%